Effectiveness of Video Self-Modeling on Hope and Daily Activities of Indonesian Youth - Nur'aini Azizah; Peter Dowrick; Tri Lestari (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2023)
Individuals who struggle with low hope tend to experience difficulties in multiple dimensions, encompassing physical, psychological, and social aspects. Despite the development of hope concepts and interventions since the mid-1990s, there has been no specific research using video self-modeling (VSM) instruments to change an individual's aspirations. Therefore, this research aimed to analyze the effectiveness of VSM on the hope and daily activities of Indonesian youth. An experimental method with a multiple-baseline design was employed. As many as 5 participants from Indonesia were selected based on pre-screening hope scale scores, specifically those showing low domain points about activities associated with family, romantic, social, academic, work, or leisure time. The data were analyzed using visual inspection by comparing scores before and after VSM intervention. The results showed that all participants demonstrated an increase in the frequency of activities they preferred. It was also found that VSM can indirectly impact the improvement of hope. This technology can be an effective intervention to assist young individuals in achieving goals and enhancing their hope.